2001
DOI: 10.1038/sj.jhh.1001238
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of digital blood pressure measured with the Omron F3 device as an index of brachial arterial pressure, under different thermal and hormonal conditions

Abstract: Background: Devices that record from the finger have potential practical advantages for home monitoring of blood pressure. However, digital arterial pressure may vary substantially from that in the brachial artery, due to the influence of peripheral wave reflection. Aims: (1) To compare digital arterial pressure, as measured with the Omron F3 device, with brachial arterial pressure and (2) to determine the effect on digital pressure of changing local vascular resistance. Method: The subjects were normotensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Arterial blood pressure becomes "damped" as blood moves from the large vessels, like the aorta, to the smaller vessels due to changes in vascular resistance. 22 Wrist monitors may overestimate systolic and diastolic blood pressures by as much as 16 and 7 mm Hg, respectively. 18,23 Studies have not shown finger monitors to be any more accurate.…”
Section: Ambulatory and Home Monitoring Of Blood Pressurementioning
confidence: 98%
“…Arterial blood pressure becomes "damped" as blood moves from the large vessels, like the aorta, to the smaller vessels due to changes in vascular resistance. 22 Wrist monitors may overestimate systolic and diastolic blood pressures by as much as 16 and 7 mm Hg, respectively. 18,23 Studies have not shown finger monitors to be any more accurate.…”
Section: Ambulatory and Home Monitoring Of Blood Pressurementioning
confidence: 98%